Identification of potential serum biomarkers for molar pregnancy and gestational choriocarcinoma using 2DGel electrophoresis/ MALDI-TOF / Farah Amalina Mohamed Affandi - Mohamed Affandi, Farah Amalina (2019)
Gestational trophoblastic disease (GTD) is a variety of cellular proliferation arising from the placental villous trophoblast. It comprises a group of disorders of benign conditions such as hydatidiform moles, molar pregnancy and the malignant forms such as invasive mole, choriocarcinoma (CC), placental site trophoblastic tumour (PSTT) and epithelioid trophoblastic tumour (ETT). Currently, GTD can only be diagnosed with a high hCG level, ultrasound, an imaging test, pelvic and histopathological examination. Limited studies have been done to determine the specific biomarkers in different types of trophoblastic diseases. This study aims to investigate the potential serum biomarkers for GTD especially molar pregnancy and choriocarcinoma. Briefly, serum samples collected from 24 normal pregnant women, 12 molar pregnancy patients, and 4 choriocarcinoma patients were subjected to measurement of hCG levels using ELISA, followed by 2D-Gel Electrophoresis (2D-GE). The results obtained from 2D-GE were then compared against normal pregnancy and analysed using Progenesis Same spot software (Nonlinear dynamics). Differentially expressed protein spots were then excised and identified using MALDI-TOF Mass Spectrometry. The findings showed that 9 significantly different proteins have been identified from the comparisons made against normal pregnancy. Alpha-1-acid glycoprotein, Ig gamma-1 chain C region, Clusterin were upregulated while Serotransferrin and Ig gamma-3 chain C region were downregulated in molar pregnancy. Apolipoprotein A-1, Ig kappa chain C region, Haptoglobin were upregulated while human serum albumin was downregulated in gestational choriocarcinoma. In conclusion, identification on the presence of these specific serum markers other than hCG in GTD will enable the physicians for early diagnosis, therapy and consequently allow complete remission of the disease. Extensive studies should be done to further investigate the roles of these proteins in the pathogenesis of GTD.